NRAS Mutations Are Rare in Colorectal Cancer - Irahara, Natsumi (2010)
Activating mutations in members of the RAS oncogene family (KRAS, HRAS and NRAS) have been found in a variety of human malignancies, suggesting a dominant role in carcinogenesis. In colon cancers, KRAS mutations are common and clearly contribute to malignant progression. The frequency of NRAS mutations and their relationship to clinical, pathologic, and molecular features remains uncertain. We developed and validated a Pyroseqencing assay to detect NRAS mutations at codons 12, 13 and 61. Utilizing a collection of 225 colorectal cancers from two prospective cohort studies, we examined the relationship between NRAS mutations, clinical outcome, and other molecular features, including mutation of KRAS, BRAF, and PIK3CA, microsatellite instability (MSI), and the CpG island methylator phenotype (CIMP). Finally, we examined whether NRAS mutation was associated with patient survival or prognosis. NRAS mutations were detected in 5 (2.2%) of the 225 colorectal cancers and tended to occur in left-sided cancers arising in women, but did not appear to be associated with any of the molecular features that were examined.